Large-scale log compressing system based on differential compression - Qiu TANG; Lei JIANG; Qiong DAI (Tongxin xuebao)
The scale of log data produced by the large scale information system is growing rapidly.It leads to the big challenge of line-speed compressing and saving the large scale log data.By analysis on massive network log data,it is found that the log data has redundant pattern in terms of log structure and time local similarity in terms of log content.A differential log compression architecture based on template is proposed.Fine-grained differential compressive strategies in the architecture can be configured for a special log data.Experimental results show that,compared with gizp,the proposed log compressing architecture improves 2～10 times’ compressive speed and gain a better compressing ratio approaching to 10%.